Considerations in Understanding Vaccine Effectiveness - Chin Shern Lau; Tar Choon Aw (Vaccines, 2022)
Although vaccine effectiveness reports are essential to assessing policies on SARS-CoV-2 vaccination, several factors can affect our interpretation of the results. These include the waning of antibodies, the prevailing viral variants at the time of the study, and COVID-19 disease prevalence in the population. Disease prevalence significantly impacts absolute risk reduction and could skew expected efficacy when increased disease prevalence inflates the absolute risk reduction in the face of a constant relative risk reduction. These factors must be considered in the interpretation of vaccine effectiveness to better understand how vaccines can improve disease prevention among the population. We highlight the impact of various factors on vaccine effectiveness.